The neural processing of pitch accents in continuous speech. (30th July 2021) - Llanos, Fernando; German, James S.; Gnanateja, G. Nike; Chandrasekaran, Bharath
Abstract: Pitch accents are local pitch patterns that convey differences in word prominence and modulate the information structure of the discourse. Despite the importance to discourse in languages like English, neural processing of pitch accents remains understudied. The current study investigates the neural processing of pitch accents by native and non-native English speakers while they are listening to or ignoring 45 min of continuous, natural speech. Leveraging an approach used to study phonemes in natural speech, we analyzed thousands of electroencephalography (EEG) segments time-locked to pitch accents in a prosodic transcription. The optimal neural discrimination between pitch accent categories emerged at latencies between 100 and 200 ms. During these latencies, we found a strong structural alignment between neural and phonetic representations of pitch accent categories. In the same latencies, native listeners exhibited more robust processing of pitch accent contrasts than non-native listeners. However, these group differences attenuated when the speech signal was ignored. We can reliably capture the neural processing of discrete and contrastive pitch accent categories in continuous speech. Our analytic approach also captures how language-specific knowledge and selective attention influences the neural processing of pitch accent categories. Highlights: We modeled EEGs time-locked to pitch accents in continuous speech. Time-locked neural responses preserve phonological contrasts between pitch accent categories. Native listeners show more robust neural discrimination of pitch accents than non-native listeners. Language group differences in pitch accent processing attenuate when speech is ignored.